2013
DOI: 10.1016/j.phrp.2013.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Selection of Multilocus Variable-Number Tandem-Repeat Analysis Primers for Genotyping Brucella abortus Biovar 1 Isolated from Human Patients

Abstract: ObjectivesBrucellosis is the most common bacterial zoonosis in the world. Multilocus variable-number tandem-repeat (VNTR) analysis (MLVA) is a molecular method for genotyping bacterial species. Brucella abortus biovar I was isolated from most of the brucellosis-suspected patients in Korea. This study was conducted to investigate the ability of various MLVA primers that are used for molecular typing B. abortus isolates and for analyzing their epidemiological data.MethodsA total of 80 human isolates of B. abortu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Although the culture strategy is hampered by the slow growing features of Brucella species, safety problems, and the reduced sensitivity of the method for detecting chronic cases, isolation of the organism remains a diagnostic cornerstone. Recovery of the brucellae is an irrefutable evidence of the disease; it permits speciation and typing of the recovered strain for epidemiological studies [1] and enables determination of antibiotic susceptibility, when indicated. Blood cultures may also allow diagnosis of brucellosis in the acute period of the disease, when serological test results may still be negative or exhibit borderline antibody titers [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although the culture strategy is hampered by the slow growing features of Brucella species, safety problems, and the reduced sensitivity of the method for detecting chronic cases, isolation of the organism remains a diagnostic cornerstone. Recovery of the brucellae is an irrefutable evidence of the disease; it permits speciation and typing of the recovered strain for epidemiological studies [1] and enables determination of antibiotic susceptibility, when indicated. Blood cultures may also allow diagnosis of brucellosis in the acute period of the disease, when serological test results may still be negative or exhibit borderline antibody titers [2].…”
Section: Introductionmentioning
confidence: 99%